The other-race effect in 3-year-old German and Cameroonian children - Suhrke, Janina; Freitag, Claudia; Lamm, Bettina; Teiser, Johanna; Fassbender, Ina; Poloczek, Sonja; Teubert, Manuel; Voehringer, Isabel A.; Keller, Heidi; Knopf, Monika; Lohaus, Arnold; Schwarzer, Gudrun (Frontiers in Psychology, 2014)
Recognizing individual faces is an important human ability that highly depends on experience. This is reflected in the so called other-race effect; adults are better at recognizing faces from their own ethnic group, while very young infants do not show this specialization yet. Two experiments examined whether 3-year-old children from two different cultural backgrounds show the other-race effect. In Experiment 1, German children (N = 41) were presented with a forced choice paradigm where they were asked to recognize female Caucasian or African faces. In Experiment 2, 3-year-olds from Cameroon (N = 66) participated in a similar task using the same stimulus material. In both cultures the other-race effect was present; children were better at recognizing individual faces from their own ethnic group. In addition, German children performed at a higher overall level of accuracy than Cameroonians. The results are discussed in relation to cultural aspects in particular.